Colony life history of the tropical arboreal ant, Cephalotes goniodontus De Andrade, 1999 - Butler, I A E; Butterfield, T; Janda, M; Gordon, D M (Insectes sociaux, 2024)
UNLABELLED: Arboreal ants are ecologically important in tropical forests, but there are few studies using DNA markers to examine their population and colony structure. Colonies of the arboreal turtle ant Cephalotes goniodontus create trail networks through the canopy of the tropical forest, in dense vegetation where it is difficult to determine how long a nest is used and how neighboring colonies partition space. We monitored 53 nest sites for up to six years and, using seven microsatellite markers, genotyped samples of workers collected at or near 41 nests over 1-4 years. We calculated average relatedness within samples collected at a given location, and between samples collected at the same location in successive years, and performed pedigree analysis to predict the number of queens that produced each sample of workers. Fifteen samples were highly related (r ≥ 0.6) from single colonies, of which 11 were monogynous and the remaining four had two queens; 19 were of intermediate relatedness (0.1 ≤ r < 0.6) with 1-6 queens, and 7 were groups of unrelated workers (r < 0.1) from at least 4 queens. Colonies persisted at the same nest site for 2-6 years. The smallest distance we found separating nests of different colonies was 16.2 m. It appears that different colonies may share foraging trails. Our study demonstrates the feasibility of using a cost-efficient genotyping method to provide information on colony structure and life history of ant species. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00040-024-00974-3.
Keywords: Cephalotes; Microsatellites; Relatedness; Arboreal ants